Gestão eletrônica de documentos: estado da arte em arquivologia - SILVA, Nadiane Carla de Oliveira (2018)
State of the art Electronic Management of Documents – GED, in order to understand it through scientific articles in 8 (eight) journals in the fields of archival science and information science. The research is qualitative, quantitative and bibliographical nature. Of data collection, it is understandable if publications in 1985 period to 2016. 77 (seventy-seven) were selected considering literature 6 (six) specific terminologies: Technology and Society, Archival Science, Technological Advances, Document Preservation, Digital Certification and Electronic Document Management. It is concluded that the GED has been discussed and established over the decades, derived from the consequences of technological advances and its challenges, being accessible and structured to a convenient management of information.